Wargaming as a Methodology: The International Crisis Wargame and Experimental Wargaming. (August 2021) - Schechter, Benjamin; Schneider, Jacquelyn; Shaffer, Rachael
Background: Wargaming has a long history as a tool for understanding the complexity of conflict. Although wargames have shown their relevance across topics and time, the immersive nature of wargames and the guild-like communities that surround them have often resisted the social scientific advances that occurred alongside the evolution of warfare. However, recent work raises new possibilities for integrating wargaming practices and social scientific methods. Purpose: Develop the experimental wargaming method and practice. Prioritizing the focus on iteration, control, and generalizability within experimental design can provide new opportunities for wargames to answer broader questions about decision-making, crisis behaviors, and patterns of outcomes. Method: The International Crisis Wargame developed in 2018 demonstrates the viability of experimental wargaming, and models the process of theorizing, designing, developing, and executing these wargames. It also identifies what makes games more or less experimental and details how experimental design influenced choices in the game. Conclusion: Experimental wargames are a promising new tool for both thesocial science and the wargaming communities. A proposed new research agenda for experimental design within wargames would support this nascent method